Variasi Pola Unsur Fungsional Judul Cerpen dalam Surat Kabar Kompas: Kajian Sintaksis: Linguistik - Arum Rindu Sekar Kasih (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2022)
The title of the short story is a representation from the contents of the short story. The patterns in the short story titles can beviewed from a syntax. This study takes several short stories in the Kompas daily newspaper and then describes the functionalelements. The functional element is the position of a unified sentence, each of which occupies a function. From the research that has been done, the patterns found in this study, among others, are in the form of a pattern of S-P (subject-predicate), P-O (object-predicate), S-P-K (subject-predicate-description), S-P-O (subject-predicate-description). ), P-S-O (predicate-subject- object), and the actual order sentence pattern. Each of the existing patterns can actually show that in giving the title to the short story, the author has his own style which he uses as a characteristic.